Host cellular microRNA involvement in the control of hepatitis B virus gene expression and replication - Mizuguchi, Yoshiaki (World J Hepatol, 2015)
A large number of studies have demonstrated that the synergistic collaboration of a number of microRNAs (miRNAs), their growth factors and their downstream agents is required for the initiation and completion of pathogenesis in the liver. miRNAs are thought to exert a profound effect on almost every aspect of liver biology and pathology. Accumulating evidence indicates that several miRNAs are involved in the hepatitis B virus (HBV) life cycle and infectivity, in addition to HBV-associated liver diseases including fibrosis, cirrhosis and hepatocellular carcinoma (HCC). In turn, HBV can modulate the expression of several cellular miRNAs, thus promoting a favorable environment for its replication and survival. In this review, we focused on the involvement of host cellular miRNAs that are directly and indirectly associated with HBV RNA or HBV associated transcription factors. Exploring different facets of the interactions among miRNA, HBV and HCV infections, and the carcinogenesis and progress of HCC, could facilitate the development of novel and effective treatment approaches for liver disease.